Influence of Artery Straightening on Local Hemodynamics in Left Anterior Descending (LAD) Artery after Stent Implantation - Pengfei Liu; Xiaoyan Deng; Xiao Liu; Anqiang Sun; Hongyan Kang (Cardiology Research and Practice)
Objectives. The study investigates local hemodynamic environment changes caused by straightening phenomenon and the relationship between straightening phenomenon and in-stent restenosis. Background. Intravascular intervention is an effective treatment in restoring the normal flow conditions and vascular lumen. Unfortunately, in-stent restenosis often occurs in a subset of patients after stent implantation and limits the success of stent implantation outcomes. The implanted stent usually causes artery straightening locally, rather than coinciding and adjusting to the physiological curve exactly. Artery straightening would apparently modify the artery geometry and therefore alter the local hemodynamic environment, which may result in intimal hyperplasia and restenosis after stenting implantation. Methods. In the current investigation, we verify the hypothesis that the artery straightening influences the local hemodynamic state using the different 3D CT models. Flow analysis for blood in the left anterior descending coronary artery and the straightening model is simulated numerically. Result. The current results reveal that the straightening phenomenon alters the distribution of wall shear stress and flow patterns, decreases the wall shear stress (WSS), and increases the oscillatory shear index (OSI) and the relative residence time (RRT), especially at the proximal and distal areas of stenting. Conclusions. The local straightened geometry established after stent implantation was likely to generate portions of the stenting area to a high risk of neointimal hyperplasia and subsequent restenosis.